IDENTIFICATION AND HIERARCHIZATION OF CRITERIA AND SUBCRITERIA FOR SELECTING SUPPLIERS IN A ROAD CONCESSIONAIRE USING THE ANALYTIC HIERARCHY PROCESS (AHP) METHOD - Leonesi, Tiago; Terazzi, Luis Fernando (Revista Interface Tecnológica, 2020)
Routinely organizations are faced with some type of problem that requires decision analysis, and it is often necessary to make judgments, which is not an easy task. Thus, when it comes to selecting a supplier, there are many criteria to be analyzed. Thus, the objective of this research is to identify and prioritize criteria and sub-criteria for the selection of suppliers through the AHP method in a large highway concessionaire in the city of Bebedouro / SP. To this end, a quantitative approach with mathematical modeling was adopted, with data and judgments made by three stakeholders involved in the subject. The modeling of the judgments was performed with the aid of the free software SuperDecisions. It took two meetings divided into two days to present the AHP method, build the hierarchical structure, and judge the criteria and sub-criteria. The survey identified three essential criteria and six sub-criteria for selecting suppliers at the target company. The result indicated the Cost criterion as the most important and in the hierarchy, the subcriteria Price, Meet deadline and Product were the ones that stood out the most.
Keywords: Analytic Hierarchy Process; Highway Concessionaire; Logistics